2013
DOI: 10.37285/ijpsn.2013.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In vitro Bioequivalence Evaluation of Different Brands of Amoxicillin Capsules Marketed in Tigray, Ethiopia

Abstract: The availability of multisource generic brands of amoxicillin in the market today places health professionals and patients in a difficult situation about the choice of a suitable product among numerous generic brands. The purpose of this study was to estimate the bioequivalence of amoxicillin capsules marketed in Ethiopia using in vitro tests in order to determine their interchangeability. The in vitro dissolution study was carried out on the six brands of amoxicillin capsules according to USP guidelines. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The statistical comparison of release profiles of amlodipine besylate tablets indicated that there is no significant difference between the generic brands and Norvasc (p < 0.05). Similar results were recorded for the capsule formulations; however, ABC-3 differed significantly from the innovator, Amlor (p > 0.05), which was found in another study (40). This difference in might indicate reduced in vivo bioavailability and bioequivalence of the products (27).…”
Section: Dissolution Testsupporting
confidence: 72%
“…The statistical comparison of release profiles of amlodipine besylate tablets indicated that there is no significant difference between the generic brands and Norvasc (p < 0.05). Similar results were recorded for the capsule formulations; however, ABC-3 differed significantly from the innovator, Amlor (p > 0.05), which was found in another study (40). This difference in might indicate reduced in vivo bioavailability and bioequivalence of the products (27).…”
Section: Dissolution Testsupporting
confidence: 72%
“…The dissolution profiles of the six drug products were statistically compared by using two independent-model parameters, the difference factor f1 and similarity factor f2. These factors were calculated from the obtained data from the drug dissolution studies of the six drug products using equations 4 and 5, respectively [15]. The difference factor, f1, is the average difference between all the points of sampling between two brands: the reference brand and one of the five test brands.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that some multisource amoxicillin capsules marketed in developing countries were not bioequivalent to the innovator product (15)(16)(17). According to the WHO, multisource pharmaceutical products that are not bioequivalent (and thus, not therapeutically equivalent) are not considered interchangeable to innovator product (18).…”
Section: A Gc2mentioning
confidence: 99%